CompTIA Data+ (DA0-001) Cert Prep: 5 Data Governance, Quality, and Controls. - Chapple, Mike (linkedin.com, 2021)
Explore the world of data governance as you prepare for the CompTIA Data+ (DAO-001) exam. Learn about data stewardship responsibilities, maintaining data quality, and more.